International comparison of stock market valuation: Evidence from a new index - Axel Jochem; Stefan Reitz (Kiel Institute for the World Economy (IfW), 2013)
This Kiel Policy Brief demonstrates the calculation of a new stock market index informing about the price competitiveness of a country's assets vis-à-vis its foreign competitors. In line with the portfolio balance approach we empirically identify net foreign holdings of a country's assets as the long-run driver of the index dynamics. Both, the index and its fundamental value are discussed for a number of important economies shading new light on the relative assessment of financial assets on international capital markets.
Keywords: F31; G15; E58; 330; Real Effective Exchange Rate; Capital Flows; Financial Markets